Does resistance training simulate cardiac muscle hypertrophy? - Bloomer, R. J. (Strength and Conditioning Journal, 2003)
When collectively considering the available data, it appears that RT is associated with a slight degree of concentric hypertrophy, which may be accentuated by AAS use. However, it should be understood that the majority of studies reviewed did not employ true experimental designs; therefore, the possibility that subjects could have varied their training and drug intake periods requires attention. Further, because data are so variable across studies, it is difficult to assert the precise extent and pattern of LV remodeling, and even more difficult to assess the potential clinical consequences for strength athletes. It should be understood that the absolute physiological increases noted in most investigations are clinically nonsignificant compared with untrained individuals when appropriately indexed and may possibly be more related to the greater degree of lean body mass within a population of strength-trained athletes than actual training itself. Further, these increases are considerably less than those found in patients with valvular disorders, hypertension, or hypertrophic cardiomyopathy and remain well within normal clinical limits. In fact, values observed for RT athletes are far below those identified as outer limits in athletes involved in endurance disciplines (34). This appears true for both men and women, in addition to athletes using AAS. Therefore, if long-term RT is a stimulus for cardiac hypertrophy, it is at best a mild one. It follows that RT is an activity that should be utilized by all who are capable of performing, as the benefits are multiple when carried out in a prudent manner.